Encyclopedia of Life Sciences 2006
DOI: 10.1002/9780470015902.a0005636
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Termination for Fetal Abnormality: Psychosocial Consequences

Abstract: Short‐ and longer‐term emotional and social sequelae are to be expected after a termination of pregnancy for fetal abnormality. It may be possible to identify couples who need extra support or intervention in order to learn to live with their decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…(Gammeltoft et al, 2008; Menary, 1987). In contrast, men in two studies reported fewer fears and vulnerabilities, and a shorter duration of negative emotions compared to women (Leuthner et al, 2003; White‐Van Mourik, 1989). Parents' willingness to only consider a future pregnancy if there is zero probability of fetal anomalies coupled with the limitations of current medicine to predict and control risks inherent to reproduction with absolute certainty, was another reason they reported for not embarking on a subsequent pregnancy (Kelly, 2009; Rillstone, 1999).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…(Gammeltoft et al, 2008; Menary, 1987). In contrast, men in two studies reported fewer fears and vulnerabilities, and a shorter duration of negative emotions compared to women (Leuthner et al, 2003; White‐Van Mourik, 1989). Parents' willingness to only consider a future pregnancy if there is zero probability of fetal anomalies coupled with the limitations of current medicine to predict and control risks inherent to reproduction with absolute certainty, was another reason they reported for not embarking on a subsequent pregnancy (Kelly, 2009; Rillstone, 1999).…”
Section: Resultsmentioning
confidence: 95%
“…Nineteen studies (Baillie et al, 2000; Brandenburg et al, 1992; Bryar, 1997; Carolan & Hodnett, 2009; Dallaire et al, 1995; Evers‐Kiebooms et al, 1988; Fernandes et al, 2020; Gammeltoft et al, 2008; Hammond et al, 2021; Irani et al, 2019; Jones et al, 1984; Kelly, 2009; Leuthner et al, 2003; Menary, 1987; Ndjapa‐Ndamkou et al, 2013; Pelly, 2003; Rillstone, 1999; White‐Van Mourik, 1989; Wollenschein et al, 2007) highlighted the reasons why parents were reluctant to become pregnant again following a diagnosis of a fetal anomaly in a previous pregnancy. For these parents, the fear of the anomaly recurring and reliving the trauma was sufficient to prevent them from becoming pregnant again (Baillie et al, 2000; Brandenburg et al, 1992; Bryar, 1997; Carlsson & Mattsson, 2018; Fernandes et al, 2020; Ferreira da Costa et al, 2005; Gammeltoft et al, 2008; Hammond et al, 2021; Irani et al, 2019; Kelly, 2009; Leuthner et al, 2003; Menary, 1987; Rillstone, 1999; White‐Van Mourik, 1989). This fear also persisted in parents whose children received a normal diagnosis following detailed investigations (Baillie et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations